(untitled) (Web of Teachers: Inderscience Research, 2024)
This article explores bilingualism as a phenomenon of alternating language use and its influence on linguistic identity, with a focus on interference at phonetic, lexical, grammatical, and stylistic levels. Drawing on studies from various languages, it highlights how linguistic and cultural differences impact bilingual communication. The paper discusses natural and artificial bilingualism, common challenges in language transfer, and strategies to address linguistic interference in foreign language education. An interdisciplinary approach combining linguistic theory and pedagogical practices is proposed to foster authentic bilingual competence and enhance intercultural communication.